The Emerging Role of Curcumin in the Modulation of TLR-4 Signaling Pathway: Focus on Neuroprotective and Anti-Rheumatic Properties - Panaro, Maria Antonietta (Int J Mol Sci, 2020)
Natural products have been used in medicine for thousands of years. Given their potential health benefits, they have gained significant popularity in recent times. The administration of phytochemicals existed shown to regulate differential gene expression and modulate various cellular pathways implicated in cell protection. Curcumin is a natural dietary polyphenol extracted from Curcuma Longa Linn with different biological and pharmacological effects. One of the important targets of curcumin is Toll-like receptor-4 (TLR-4), the receptor which plays a key role in the modulation of the immune responses and the stimulation of inflammatory chemokines and cytokines production. Different studies have demonstrated that curcumin attenuates inflammatory response via TLR-4 acting directly on receptor, or by its downstream pathway. Curcumin bioavailability is low, so the use of exosomes, as nano drug delivery, could improve the efficacy of curcumin in inflammatory diseases. The focus of this review is to explore the therapeutic effect of curcumin interacting with TLR-4 receptor and how this modulation could improve the prognosis of neuroinflammatory and rheumatic diseases.